Solid waste incineration modelling for advanced moving grate incinerators - Jiang, Mingtao (2021)
Currently, the design of advanced moving grate (AMG) incinerators for solid waste is aided by computational simulations. The simulation approach couples a waste bed model to characterize the incineration processes of the waste material on top of the moving grate, with a computational fluid dynamics (CFD) model to reproduce the heated air movement and reactions in the incinerator space above. However, the simulation results of AMG incinerators are rarely compared with actual field measurements for validation in the literature so far. In this study, we first examine the sensitivity of pyrolysis kinetics in the waste bed model using three existing alternatives. The predictions of combustion characteristics, including the bed height, flow and temperature distributions, composition of stack gases and gas emissions are obtained for the three alternatives and compared with measurements from a simple laboratory furnace. The results show that the pyrolysis kinetics mechanism can significantly affect the outputs from the waste bed model for incineration modelling. Subsequently, we propose a new coupling approach based on a recent AMG waste bed model (which includes the complex pyrolysis kinetics inside the waste bed on top of the moving grate) and the freeboard CFD simulations. The new approach is then used to predict the field performance of a large scale waste-to-energy (WTE) plant and the predictions are compared directly with the real measurements in various operational scenarios. The comparison shows an overall satisfactory agreement in terms of temperature and exit gases composition given the complexity of the real life operations, although the CO emission is slightly underpredicted.